Cognitive deficits and coronary calcium levels in hypertension on the background of bronchial asthma - L. A. Mubinova; V. A. Razin (Лечащий Врач, 2024)
Background. The article presents the results of a study to identify cognitive deficits in patients based on the level of coronary calcium with concomitant pathology in the form of hypertension and bronchial asthma. Currently, it is believed that a long-term increase in blood pressure, which does not have proper correction, leads to cognitive impairment. At the same time, bronchial asthma, in the absence of proper therapy, in the case of reduced adherence to treatment and as a result of the occurrence of chronic hypoxia of the brain, the disease affects cognitive functions. It has been repeatedly proven that an increase in the calcium index in combination with concomitant comorbidity worsens brain perfusion, which undoubtedly affects cognitive functions.Objective. The purpose of this study is to evaluate coronary calcium and cognitive deficits in comorbid patients with arterial hypertension and bronchial asthma. In the course of the work, 83 patients with comorbid conditions of hypertension and BA were examined, tested according to these scales and calculated the calcium index, which allowed us to obtain the following results.Results. The calcium index (Agaston index) in group I with (AH) 41.2 ± 32.1; in group II with AH and BA 91.0 ± 45.2, in group III conditionally healthy – 7.1 ± 2.1. The Montreal Cognitive Function Assessment Scale (MoSA) and the Short Mental Status Assessment Scale (MMSE) were used to assess the level and presence of initial cognitive impairment. According to the MoHS scale, patients with arterial hypertension scored 27.4 ± 1.7 points. The group of patients with bronchial asthma in combination with arterial hypertension scored an average of 26.5 ± 1.6 points, the control group scored 28.1 ± 1.4 points. According to the MMSE scale: in group I, patients with arterial hypertension received 28.7 ± 0.9 according to the results of the survey; in group II with a combination of arterial hypertension and bronchial asthma – 28.1 ± 1.2 points, in group III conditionally healthy patients – 29.3 ± 0.8 points.